Proceedings of the Eleventh Annual Symposium on Computational Geometry - SCG '95 1995
DOI: 10.1145/220279.220286
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sequential Delaunay triangulation algorithms

Abstract: This paper presents an experimental comparison of a number of different algorithms for computing the Deluanay triangulation. The algorithms examined are: Dwyer's divide and conquer algorithm, Fortune's sweepline algorithm, several versions of the incremental algorithm (including one by Ohya, Iri, and Murota, a new bucketing-based algorithm described in this paper, and Devillers's version of a Delaunay-tree based algorithm that appears in LEDA), an algorithm that incrementally adds a correct Delaunay triangle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 31 publications
1
53
0
1
Order By: Relevance
“…We therefore considered distributions motivated by different domains, such as the distribution of stars in a flat galaxy (Kuzmin) and point sets originating from mesh generation problems. The density of our distributions may vary greatly across the domain, but we observed that the resulting triangulations tend to contain relatively few bad aspect-ratio triangles-especially when contrasted with some artificial distributions, such as points along the diagonals of a square [1]. Indeed, for the case of uniform distribution, Bern et al [31] provided bounds on the expected worst aspect ratio.…”
Section: Data Distributionsmentioning
confidence: 79%
See 4 more Smart Citations
“…We therefore considered distributions motivated by different domains, such as the distribution of stars in a flat galaxy (Kuzmin) and point sets originating from mesh generation problems. The density of our distributions may vary greatly across the domain, but we observed that the resulting triangulations tend to contain relatively few bad aspect-ratio triangles-especially when contrasted with some artificial distributions, such as points along the diagonals of a square [1]. Indeed, for the case of uniform distribution, Bern et al [31] provided bounds on the expected worst aspect ratio.…”
Section: Data Distributionsmentioning
confidence: 79%
“…The data files are available upon request if a different definition of work is of interest. Although floating-point operations certainly do not account for all costs in an algorithm they have the important advantage of being machine independent (at least for machines that implement the standard IEEE floating-point instructions) and seem to have a strong correlation to running time [1], at least for algorithms with similar structure.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations